2015
DOI: 10.4300/jgme-d-14-00205.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Outcomes of Electronic Tools Supporting Physician Shift-to-Shift Handoffs: A Systematic Review

Abstract: Background Multiple organizations have recognized that handoffs are prone to errors, and there has been an increase in the use of electronic health records and computerized tools in health care. Objective This systematic review evaluates the current evidence on the effectiveness of electronic solutions used to support shift-to-shift handoffs. Methods We searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…As other reviews of these topics have found, 24,47,48,56,79,84,89,[95][96][97][98]112,116 there is a mixed picture with regard to study results in all four interventions. There are a number of possible explanations for this.…”
Section: Limitationsmentioning
confidence: 88%
See 2 more Smart Citations
“…As other reviews of these topics have found, 24,47,48,56,79,84,89,[95][96][97][98]112,116 there is a mixed picture with regard to study results in all four interventions. There are a number of possible explanations for this.…”
Section: Limitationsmentioning
confidence: 88%
“…The majority of studies in the four systematic reviews found that handover tools were associated with an improvement in at least one outcome ( Tables 8 and 9). [95][96][97][98] Examples of improvements included decreases in the number of dropped tasks, the number of omissions, the number of preventable adverse events and LOS. However, there were also a small number of studies that reported an increase in the number of unexpected changes in care and the number of errors attributed to handover.…”
Section: Standardised Handover Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Electronic sign-out applications are tools used as standalone or integrated with the electronic medical record to ensure a structured transfer of patient information during healthcare provider handoffs. Two systematic reviews 19 , 20 evaluating outcomes of electronic tools supporting physician shift-to-shift handoffs concluded that most studies supported using an electronic tool with an improvement in the process of handover, fewer omissions of critical patient information and reduced handover time when using the electronic tool with few low-quality studies assessing patient outcome measures. The authors in both reviews also noted that a significant number of the included studies were not well designed and further evaluation using rigorous study designs is needed.…”
Section: Electronic Sign-out and Hand-off Toolsmentioning
confidence: 99%
“…We obtained all of the articles included in systematic reviews of the handoffs literature published from 2013 to March 2016. Of the articles reviewed (198), only 34.7% (Abraham et al, 2014;Davis et al, 2015;Flemming & Hubner, 2013;T. Mardis et al, 2016;Masterson, Gill, Turner, Shrichand, & Giuliani, 2013;Moller et al, 2013;Pucher et al, 2015;Robertson, Morgan, Bird, Catchpole, & McCulloch, 2014;Sherman, Sand-Jecklin, & Johnson, 2013) reported any funding (Table 2).…”
Section: The Badmentioning
confidence: 99%